Matrix models of bar graph data display for bicyclic excitation of the optoelectronic scale - Bushma, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
In this work, being based on the theory of sets and matrix formulation of the information area for a bar graph display the author obtained a matrix description for electric signals necessary to form two variants of bicyclic excitation of the optoelectronic scale elements under dynamic realization of a bar graph information model.